Assessment of Writing Errors and Peer Review Process of Accepted Abstracts in the 13th Annual Research Congress of Iranâ€™s Medical Sciences Students: - Khani, Afshin; Izadpanah, Fatemeh; Zarghami, Amin; Mahdizadeh, Hamid; Khafri, Soraya (Galen Medical Journal, 2014)
Background: Despite more than a decade experience of annual student congresses in Iran, major scientific writing weakness still exists in studentsâ€™ abstracts submitted to the Annual Research Congress of Iranâ€™s Medical Sciences Students (ARCIMSS). Assessment of these abstracts can provide information on common scientific writing errors and subsequent development of abstract quality for the future congresses. Assessment of writing errors and peer review process of accepted abstracts in ARCIMSS 13th forms the central idea of the present study. Materials and Methods: In this cross-sectional study, from all 505 accepted abstracts, 17 abstracts were excluded and the remaining 488 abstracts were evaluated for affiliation and educational level of the presenter, presentation type, writing errors and the scores of reviewing process for each abstract. Writing errors were compared based on the presentersâ€™ affiliation (Student Research Committee (SRC) affiliated and non-SRC affiliated) and educational level. Also, correlation between students and faculty membersâ€™ reviewing scores in peer review process was evaluated.Results: Writing errors were seen in 242 (49.6%) abstracts and the majority of errors were seen in the â€œauthorâ€™s affiliationâ€ section (26.6%). The frequency of writing errors was significantly lower in SRC-affiliated abstracts comparing to non-SRC affiliated (P=0.038) that was not significantly different from postgraduate and undergraduate presenters (P=0.34). There was no significant correlation between pre-congress and during-congress peer reviewing scores (P=0.399, r=0.05). Conclusion: There were significant writing errors in accepted abstracts. This issue underlines the necessity of educational interventions performed by SRC members in order to develop studentsâ€™ skills in abstract writing based on standard guidelines. [GMJ.2014;3(4):245-51]